Desarrollo del proyecto circuito alternativo de comercialización - CIALCO módulo captura de información y georeferenciación - Once Cordero, Alba Yadira (2017)
This work of degree allows raise the information of the CIALCOS (Alternative Circuits of Marketing) department of General Coordination of Commercial networks CGRC of Ministry of Agriculture, Livestock, Aquaculture and Fisheries. It starts with the analysis of customer requirements, explains the background and justification for this project; for the making of the system is used the methodology XP eXtreme Programming, and the tools computer of software free to the development of the system. The first chapter covers the analysis of important concepts on each of the tools and elements for the development of the software. In the second chapter, before the analysis is designed and development an agile methodology, using user stories; to specify the requirements requested by the customer is built the CRC (Class - Responsibility - Collaboration) cards with which displayed the interactions between classes. Chapter three is the construction and testing of the system; at this stage, the mistakes that are generated at the time of development the system is purged. As investigative process conclusions with the presentation of findings and recommendations, sources, bibliography and the annexes of the document.